The impact of trade openness toward economic growth in Malaysia / Mohd Raffie Roy Au Herry - Herry, Mohd Raffie Roy Au (2019)
Trade openness has contribute in Malaysia economic growth and has been in the economic literature subject of several theoretical and empirical studies. This research will analyzes the impact of trade openness on economic growth in the case of Malaysia using OLS method over the period of 1980-2017. The result show that trade openness has exert positive and significant effect on economic growths but different respond with other variable such as domestic credit, inflation and population.